Genome-wide gene expression dataset used to identify potential therapeutic targets in androgenetic alopecia - R. Dey-Rao; A.A. Sinha (Data in Brief, 2017)
The microarray dataset attached to this report is related to the research article with the title: “A genomic approach to susceptibility and pathogenesis leads to identifying potential novel therapeutic targets in androgenetic alopecia” (Dey-Rao and Sinha, 2017) [1]. Male-pattern hair loss that is induced by androgens (testosterone) in genetically predisposed individuals is known as androgenetic alopecia (AGA). The raw dataset is being made publicly available to enable critical and/or extended analyses. Our related research paper utilizes the attached raw dataset, for genome-wide gene-expression associated investigations. Combined with several in silico bioinformatics-based analyses we were able to delineate five strategic molecular elements as potential novel targets towards future AGA-therapy. Keywords: AGA, Androgenetic alopecia, Bald-scalp, Gene-expression, Microarray, CEL